A Critical Review of the Use of Wenger's Community of Practice (CoP) Theoretical Framework in Online and Blended Learning Research, 2000-2014 - Sedef Uzuner Smith; Suzanne Hayes; Peter Shea (Online Learning, 2017)
After presenting a brief overview of the key elements that underpin Etienne Wenger’s communities of practice (CoP) theoretical framework, one of the most widely cited and influential conceptions of social learning, this paper reviews extant empirical work grounded in this framework to investigate online/blended learning in higher education and in professional development. The review is based on integrative research approaches, using quantitative and qualitative analysis, and includes CoP oriented research articles published between 2000 and 2014. Findings are presented under three questions: Which research studies within the online/blended learning literature made central use of the CoP framework? Among those studies identified, which ones established strong linkages between the CoP framework and their findings? Within this last group of identified studies, what do the patterns in their use of the CoP framework suggest as opportunities for future research in online teaching and learning?